Construction and Validation of a Brief Pandemic Fatigue Scale in the Context of the Coronavirus-19 Public Health Crisis - Esther Cuadrado; Esther Cuadrado; Miguel A. Maldonado; Miguel A. Maldonado; Carmen Tabernero; Carmen Tabernero; Carmen Tabernero; Alicia Arenas; Alicia Arenas; Rosario Castillo-Mayén; Rosario Castillo-Mayén; Bárbara Luque; et al. (International Journal of Public Health, 2021)
Objectives: The chronic restrictions to mitigate the new SARS-CoV-2 virus may result in pandemic fatigue. This study set out to develop a short, reliable, valid, and gender-invariant instrument—the Pandemic Fatigue Scale (PFS).Methods: In the first phase, 300 students responded to a pilot questionnaire that allowed the reduction and refinement of the items. In the second phase, the validity, reliability, and invariance of the scale were explored among a sample of 596 participants.Results: Factor exploratory and confirmatory analyses confirmed a robust adjustment for the bifactorial structure that explained 79,36% of the variance. The two factors identified were 1) people’s demotivation in continuing to follow the recommended protective behaviors (neglect) and 2) people’s boredom regarding the pandemic-related information (boredom). The pattern of relations between the Pandemic Fatigue Scale and other variables—find through correlation, mediation, and path analyses—and the gender differences—find in the ANOVA analyses—provided strong evidence of the construct validity. Moreover, the PFS was shown to be invariant regarding gender in a multigroup factor confirmatory analysis.Conclusion: The instrument can be of utility for professionals and researchers to assess pandemic fatigue, a variable that can affect the adoption of protective measure to avoid catching and spreading the virus.